Experimental platform for waveform optimization in passive UHF RFID systems. Issue 10 (3rd August 2020) - Merakeb, Yanis; Ezzeddine, Hussein; Huillery, Julien; Bréard, Arnaud; Touhami, Rachida; Duroc, Yvan
Abstract: The article presents an experimental platform, so called "RFID Waveformer, " dedicated to the study of waveform optimization in the radio frequency identification (RFID) context. It is a flexible solution that enables waveform design and their energetic performance evaluation in a ultra high frequency (UHF) RFID link following the ISO‐18000 GEN2 standard protocol. It consists of a reader emulated by a LabVIEW interface controlling radiofrequency laboratory instruments, which perform real time tag response detection. Its interconnection with MATLAB routines enables the design and the evaluation of arbitrarily shaped RFID waveforms. In this article, for illustration, three waveforms are tested with RFID Waveformer in a complex propagation environment: pulsed wave (PW) and time reversal (TR) modes compared to the traditional continuous wave (CW) mode. Experimental results show that both PW and TR modes improve the energetic efficiency of the forward link and so the RFID read range compared to CW mode. Furthermore, TR presents the optimal efficiency in complex propagation medium. The RFID Waveformer enables tag response detection in the three modes offering ease of use and repeatability of measurements. The RFID Waveformer being not limited to the scenario considered in this article, it is a versatile solution extendable to other contexts.